Static balancer for the neck of a face robot - Cho, Changhyun; Kim, Seungjong (SAGE PUBLICATIONS LTD, 2014)
We propose a 3-degree of freedom gravity compensator for the neck of a robotic face. The neck of the face robot is configured with yaw-pitch-pitch-roll rotations. Since the yaw rotation is made parallel to gravity, only the pitch-pitch-roll rotations are considered for gravity compensation. The 1-degree of freedom gravity compensator is located at the first pitch joint. A 2-degree of freedom gravity compensator equivalent to the existing gravity compensator is proposed and applied to the second pitch and roll rotations. A parallelogram is adopted between the first and second pitch rotations. One end of the 2-degree of freedom gravity compensator is attached at the parallelogram and the other is fixed at the face. Wires are used to realize a zero-length spring for all gravity compensators and all springs are located at the base for compact design. Experimental results for gravity compensation show that gravitational torques were effectively counterbalanced by the proposed 3-degree of freedom gravity compensator.